Occurrence and Antibiotic Sensitivity of Escherichia coli and Salmonella spp. in Retail Chicken Meat at Selected Markets in Valencia City, Bukidnon, Philippines - Elumba, Zeus S.; Allera, Ma Lean M; Taganas, Resmae Rose R. (Asian Journal of Biological and Life Sciences, 2018)
Aim: Contaminated retail chicken meat has been implicated with food poisoning caused by Escherichia coli and Salmonella spp. The present study was aimed to determine the occurrence and antibiotic sensitivity of E. coli and Salmonella spp. in retail chicken meat at selected markets in Valencia City, Bukidnon, Philippines. Methods: A total of 50 retailed chicken meats which comprised of drumsticks (n=25) and wings (n=25) were collected aseptically from three selected markets (2 supermarkets and 1 wet market) in Valencia City, Bukidnon, Philippines and examined for the occurrence of Escherichia coli and Salmonella spp. Identification of bacterial isolates was through morphological characteristics, Gram-staining, and biochemical tests or growth-dependent identification methods. The antibiotic sensitivity of the pure isolates to amoxicillin (25 μg), ampicillin (10 μg), chloramphenicol (30 μg), and streptomycin (10 μg) was determined through a standard antimicrobial disk diffusion test. Results: Results revealed that 68% (17/25) of the drumsticks and 96% (24/25) of the wings samples were contaminated with E. coli while 4% (1/25) of the drumsticks and 32% (8/25) of wings samples were contaminated with Salmonella spp. In total, 41 pure isolates of E. coli and 9 pure isolates of Salmonella spp. were obtained. Antimicrobial disk diffusion test revealed that 87.80% (36/41) of E. coli isolates and 100% (9/9) Salmonella spp. isolates are resistant to amoxicillin, and 36.58% (15/41) of E. coli isolates and 88.88% (8/9) Salmonella spp. isolates are resistant to ampicillin. Moreover, 29.27% (12/41) of E. coli isolates and 88.88% (8/9) of Salmonella spp. isolates are resistant to both amoxicillin and ampicillin. Majority (96%) of isolates are sensitive to streptomycin. Conclusion: There was a high occurrence of E. coli contamination in retail chicken meat in Valencia City, Bukidnon, Philippines. E. coli and Salmonella spp. from these retail meat showed high resistance to amoxicillin and ampicillin.
Keywords: Antibiotic sensitivity; Chicken meat; Escherichia coli; Salmonella spp.